Smart Governance Decision-Support System for Fisheries Development in Southeast Maluku: A Conceptual Framework - Hasyim, Cawalinya Livsanthi; Somnaikubun, Glenty B.A; Teniwut, Wellem Anselmus (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2025)
Background: Southeast Maluku Regency has vast marine and fishery resources; hence, the fisheries sector has not been a major economic contributor. The fisheries sector is still below its maximum capacity; this problem is caused by unsustainable fishing sector development planning. Objective: This research aimed to build framework tools to help plan and manage a sustainable and integrated fisheries sector based on empirical conditions. Methods: In this research, a suitable application framework was designed to support the development and planning of the fisheries sector in this region, the design of the input process, the input used, the interface, and the output produced to achieve smart government and a smart city. Results: This study built a conceptual framework tailored to the empirical conditions of the region in terms of geographical location and limited internet coverage for the Southeast Maluku Regency fisheries supporting master plan. Conclusion: The study provides guidance for researchers and practitioners in similar small island regions worldwide to construct a web-based intelligent DSS (decision support system) consistent with geographical conditions for planning the fisheries and marine sectors in their respective regions. The conceptual framework is adaptive which based on empirical condition both data and assessment of ranking for suitability location.